Islamic Economic Mechanisms to Achieve Inclusiveness and Islamic Finance for Sustainability - Al-Isawi, Alaa Thabit Jasim (Journal of Ecohumanism, 2024)
The present study explores avenues for Islamic economics to achieve financial inclusiveness and Islamic finance to achieve sustainability. The study focuses on the importance of providing financial services to the poor as a tool for development and poverty reduction. The study also reviews impediments to poor people’s access to financial services, such as low income, high risks, high costs, and cultural and religious constraints. The present study emphasizes the importance of providing Shariah-compliant financial services to the poor in Islamic countries. The study also addresses the regulatory aspects of Islamic financial institutions and the role of zakat and waqf in achieving financial inclusion and sustainability.